Improvement of the insecticidal capacity of two Purpureocillium Lilacinum strains against Tribolium Confusum - Barra, Paula Sabina (2015)
Entomopathogenic fungi can regulate insect populations. They have extracellular enzymes that degrade cuticle components, mainly hydrocarbons, used as an energy source. The increase in insecticidal activity of fungi in a medium supplemented with cuticular hydrocarbons was assayed and the hydrolytic enzyme profiles of two strains of Purpureocillium lilacinum were evaluated. A spore suspension of P. lilacinum was inoculated in Petri plates with different values (0.99–0.97–0.95) of water activity (Aw) using the substrates gelatin, starch and tween-20. Growth rate on the different substrates and the enzymatic activity index for proteases, amylases and lipases at different incubation times, pH and Aw, was evaluated. Moreover, the insecticidal efficiency of strains grown in media supplemented with n-hexadecane and n-octacosane was analyzed. LT50 was calculated against adults of Tribolium confusum and showed that mortality increased about 15% when the strains grew in amended culture medium. High amylolytic activity was detected, but proteases were the main enzymes produced. Optimal protease production was observed in a range of acid and alkaline pH and lower Aw. The greatest growth rate was obtained in presence of gelatin. Lipase and amylase production was detected in small amounts. Fungal growth in media with hydrocarbon mixtures increased the pathogenicity of the two strains of P. lilacinum, with the strain JQ926223 being more virulent. The information obtained is important for achieving both an increase in insecticidal capacity and an understanding of physiological adaptation of the fungus.